Associations Between Health Literacy, eHealth Literacy, and COVID-19-Related Health Behaviors Among Chinese College Students: Cross-sectional Online Study - Li, Shaojie; Cui, Guanghui; Kaminga, Atipatsa Chiwanda; Cheng, Sixiang; Xu, Huilan (JMIR Publications, 2021)
BackgroundDuring the COVID-19 pandemic, the internet has significantly spread information, providing people with knowledge and advice about health protection regarding COVID-19. While a previous study demonstrated that health and eHealth literacy are related to COVID-19 prevention behaviors, few studies have focused on the relationship between health literacy, eHealth literacy, and COVID-19-related health behaviors. The latter includes not only preventative behaviors but also conventional health behaviors. ObjectiveThe objective of this study was to develop and verify a COVID-19-related health behavior questionnaire, explore its status and structure, and examine the associations between these behaviors and participants' health literacy and eHealth literacy. MethodsA snowball sampling method was adopted to recruit participants to complete anonymous cross-sectional questionnaire surveys online that assessed sociodemographic information, self-reported coronavirus knowledge, health literacy, eHealth literacy, and COVID-19-related health behaviors. ResultsOf 1873 college students who were recruited, 781 (41.7%) had adequate health literacy; the mean eHealth literacy score was 30.16 (SD 6.31). The COVID-19-related health behavior questionnaire presented a two-factor structure-COVID-19-specific precautionary behaviors and conventional health behaviors-with satisfactory fit indices and internal consistency (Cronbach α=.79). The mean score of COVID-19-related health behaviors was 53.77 (SD 8.03), and scores differed significantly (P<.05) with respect to residence, college year, academic major, family economic level, self-reported health status, having a family member or friend infected with coronavirus, and health literacy level. Linear regression analysis showed that health literacy and eHealth literacy were positively associated with COVID-19-specific precautionary behaviors (βhealth literacy=.149, βeHealth literacy=.368; P<.001) and conventional health behaviors (βhealth literacy=.219, βeHealth literacy=.277; P<.001). ConclusionsThe COVID-19-related health behavior questionnaire was a valid and reliable measure for assessing health behaviors during the pandemic. College students with higher health literacy and eHealth literacy can more actively adopt COVID-19-related health behaviors. Additionally, compared to health literacy, eHealth literacy is more closely related to COVID-19-related health behaviors. Public intervention measures based on health and eHealth literacy are required to promote COVID-19-related health behaviors during the pandemic, which may be helpful to reduce the risk of COVID-19 infection among college students.